Efficacy and Mechanism of Thymol/KGM/LG Edible Coating Solution on Inhibition of Mucor circinelloides Isolated From Okra - Zhang, Qinqiu; Qin, Wen; Hu, Xinjie; Yan, Jing; Liu, Yaowen; Wang, Zhuwei; Liu, Lang; Ding, Jie; Huang, Peng; Wu, Jiya (Frontiers in Microbiology, 2022)
With the increasing demand and quality requirement for the natural nutritious food in modern society, okra has attracted much attention because of its high nutritional value and remarkable functionality. However, the occurrence of postharvest diseases of fresh okra severely limited the application and the value of okra. Therefore, in this study, the dominant pathogens causing postharvest diseases such as soft rot were isolated from naturally decaying okra. It was identified as Mucor circinelloides by its morphological characteristics and standard internal transcribed spacer ribosomal DNA sequence. Furthermore, the biological characteristics of M. circinelloides were studied, and the inhibitory effect of thymol/KGM/LG (TKL) edible coating solution on M. circinelloides and its possible mechanism was discussed. In addition, TKL edible coating solution had a dose-dependent inhibitory effect on M. circinelloides, with a 50% inhibitory concentration (EC50) of 113.55 mg/L. The TKL edible coating solution at 960 mg/L of thymol completely inhibited mycelial growth and spore germination of M. circinelloides. The results showed that the best carbon source of M. circinelloides was maltose, the best nitrogen source was beef extract and potassium nitrate, the best pH was 6, the best temperature was 28°C, the best NaCl concentration was 0.5%, and the light was conducive to the growth of M. circinelloides. It was also observed by scanning electron microscope (SEM) that TKL was more likely to destroy the cell wall integrity of M. circinelloides, inhibit spore morphology and change mycelium structure. Meanwhile, the activity of chitinase (CHI), an enzyme related to cell wall synthesis of M. circinelloides, was significantly decreased after being treated by TKL with thymol at 100 mg/L (TKL100). The content of Malondialdehyde (MDA) in M. circinelloides decreased significantly from 12 h to 48 h, which may cause oxidative damage to the cell membrane. The activity polygalacturonase (PG), pectin methylgalacturonase (PMG), and cellulase (Cx) of M. circinelloides decreased significantly. Therefore, the results showed that TKL had a good bacteriostatic effect on okra soft rot pathogen, and the main bacteriostatic mechanism might be the damage of cell membrane, degradation of the cell wall, inhibition of metabolic activities, and reduction of metabolites, which is helpful to further understand the inhibitory effect of TKL on okra soft rot pathogen and its mechanism.